2020
DOI: 10.1177/1362361320967790
|View full text |Cite
|
Sign up to set email alerts
|

Research priorities of the autism community: A systematic review of key stakeholder perspectives

Abstract: In recent years, a shift in focus has seen researchers seek to identify the priorities and preferences of key stakeholders to shape the direction of future research for those on the autism spectrum. The process of synthesising the views, knowledge and expertise of key stakeholders with either a lived or shared experience of autism is invaluable and can inform future research to ensure that it is meaningful and has the greatest impact. A number of studies have reported on the research priorities of groups withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 36 publications
3
107
1
Order By: Relevance
“…Despite this, the evidence base on how to treat mental health problems in autism is meagre, and most autistic people with mental health problems report receiving inadequate help for these difficulties [22]. Reflecting this, research into mental health problems has been identified as a key priority for research across a variety of stakeholder groups [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, the evidence base on how to treat mental health problems in autism is meagre, and most autistic people with mental health problems report receiving inadequate help for these difficulties [22]. Reflecting this, research into mental health problems has been identified as a key priority for research across a variety of stakeholder groups [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The IACC recommended increased funding for research on lifespan issues, and autistic individuals have also expressed a desire for increased research in this area (Frazier et al, 2018;Roche et al, 2021). However, research on lifespan issues only comprised 2.51% of the autism research funding during 2017-2019.…”
Section: Discussionmentioning
confidence: 99%
“…In order to support autistic people in achieving positive long-term outcomes, it is important to further understand the presentation of mental ill-health in autism and to determine why autistic individuals are at higher risk of mental health difficulties. This is crucial since the mental health of autistic individuals has been identified as a key priority for research across multiple stakeholder groups [ 26 , 27 ].…”
Section: Study Informationmentioning
confidence: 99%